PEMANFAATAN UMBI TALAS SEBAGAI BAHAN SUBTITUSI TEPUNG TERIGU DALAM PEMBUATAN COOKIES YANG DISUPLEMENTASI DENGAN KACANG HIJAU - Welli Yuliatmoko; Dian Indrayani Satyatama (Jurnal Matematika Sains dan Teknologi, 2012)
Taro flour can be used as a wheat flour substitution in cookies making, although its quality is still relatively low, especially in terms of taste and nutritional composition. An alternative way to improve its nutritional composition is by the addition of green beans, as a protein source. This study was aimed to obtain the cookies formulation that use Lampung Taro flour enriched with green beans flour as a wheat flour substitution. The cookies were tested organoleptically by panelists using hedonic scale including color, aroma, taste, texture and general appearance. The acceptable cookies were analyzed their chemical characteristics. The results showed that Taro flour cookies with the content of 30%, 50%, and 60% Lampung Taro flour have received the best judgment from panelists. From the nutritional point these cookies were considered meet the nutritional value specified by SNI 1992 but the protein content was still below standard. The addition of 10% green beans flour was not able to improve the nutritional value of protein in the cookies. Taro flour can be used as a wheat flour substitution in cookies making, although its quality is still relatively low, especially in terms of taste and nutritional composition. An alternative way to improve its nutritional composition is by the addition of green beans, as a protein source. This study was aimed to obtain the cookies formulation that use Lampung Taro flour enriched with green beans flour as a wheat flour substitution. The cookies were tested organoleptically by panelists using hedonic scale including color, aroma, taste, texture and general appearance. The acceptable cookies were analyzed their chemical characteristics. The results showed that Taro flour cookies with the content of 30%, 50%, and 60% Lampung Taro flour have received the best judgment from panelists. From the nutritional point these cookies were considered meet the nutritional value specified by SNI 1992 but the protein content was still below standard. The addition of 10% green beans flour was not able to improve the nutritional value of protein in the cookies.